Leiomyoma of the Esophagus - Martínez, José L; Bazzino, Fernando; Formento, Ana; Gorlero, María Luisa; González, Susana; Navarrete, Héctor D; Chifflet, Juan (Cirugía del Uruguay, 1983)
A case of leiomyoma of the esophagus is present.ed. It was treated with miomectomy and mucosa! resection having good evolution. No previous report was found in Uruguayan literature. Important aspects of this non common tumoral entity are emphasized.